MODEL PEMBELAJARAN PENDIDIKAN KARAKTER DI SEKOLAH - Nancy Angelia Purba (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2017)
Character education is currently inadequately taught by traditional learning methods that tend to be based on the assumption that learners have the same needs, learning in the same way and in the same time; in the quiet classroom, with the tightly structured subject matter and it is dominant by the teacher. Traditional learning methods are considered not able to achieve the educational goals because of less accommodate the continuity of the experience of learners, especially in the age of primary school is still crave the ongoing experience in the family environment can be experienced also in school. Character education is a conscious and earnest effort of a teacher to teach the values to his students. Those values are built continuously day by day through thoughts and deeds, thought by thought, action by action. The teacher has the duty and responsibility to give guidance to the students to be fully characterized human in the dimensions of heart, mind, body, taste and intention in everyday life. So, the experience of children who are still global necessarily require the application of the relevant learning models to their characteristics. Therefore, an effective character education learning model is needed in schools.